Application Of Roguing Techniques For Seed Production In The Marsudi Among Tani Farming Group, Dawuhan Village, Banyumas District, Banyumas District : Penerapan Teknik Roguing Guna Produksi Benih Di Kelompok Tani Marsudi Among Tani Desa Dawuhan Kecamatan Banyumas Kabupaten Banyumas - Agus Riyanto; Rifki Andi Novia; Nur Kholida Wulansari; Ponendi Hidayat; Suwarto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Seeds are an important factor in plant cultivation. Marsudi Among Tani is a farmer group that specializes in cultivating the organic Mentik Susu rice variety. The availability of pure Mentik Susu seeds is a problem for this farmer group. To solve this problem, we need to apply Roguing procedures for seed production. The objective of this service activity is to enhance the the members of the Marsudi Among Tani group's knowledge, comprehension, and skill in the Roguing technique. The target audience for this activity are members of the Marsudi Among Tani farmer group, Dawuhan Village, Banyumas District, Banyumas Regency. The methods used in this activity include counseling, Roguing practice and evaluation. The results of this activity show that farmers' knowledge, understanding and skills related to Roguing techniques have increased so that the Marsudi Among Tani farmer group is able to produce Mentik Susu seeds.